Improvement effect of biochar on soil microbial community structure and metabolites of decline disease bayberry - Ren, Haiying; Guo, Hao; Shafiqul Islam, Mohammad; Zaki, Haitham E. M.; Wang, Zhenshuo; Wang, Hongyan; Qi, Xingjiang; Guo, Junning; Sun, Li; Wang, Qi; Li, Bin; Li, Gang; et al. (Frontiers in Microbiology, 2023)
Decline disease is a new disease that has recently caused severe damage in the bayberry industry. After applying biochar to treat the soil of declining diseased trees, the changes in its vegetative growth, fruit quality, soil physical and chemical properties, soil microbial community structure, and metabolites were studied to analyze the disease prevention mechanism and control. Results indicated that the application of biochar could improve the vigor of diseased trees, the fruit quality, and the diversity and species number of microbial communities at the level of phyla, orders, and genera in the rhizosphere soil. The relative abundance of bacterial Mycobacterium and Crossiella and the fungal Geminibasidium and Fusarium were significantly increased in rhizosphere soil after biochar treatment on the decline diseased bayberry. In contrast, the bacterial Acidothermus, Bryobacter, Acidibacter, and the fungal Cladophialophora, Mycena, and Rickenella significantly decreased. Analysis of redundancies (RDA) of microbial communities and soil characteristics revealed that the composition of bacterial and fungal communities in bayberry rhizosphere soil was significantly affected by the main seven, including the pH, organic matter, alkali hydrolyzable nitrogen, available phosphorus, available potassium, exchangeable calcium and exchangeable magnesium in the rhizosphere soil, and all the contribution rates to fungi larger than those to bacteria, at genus levels. The biochar greatly influenced the metabolomics distribution of rhizosphere soils from the decline disease bayberry. There were 109 different metabolites in the control of the decline disease and the treatment of biochar, mainly including acid, alcohol, ester, amine, amino acid, sterol, sugar, and other secondary metabolites, of which 52 kinds of contents were increased significantly such as aconitic acid, threonic acid, pimelic acid, epicatechin, and lyxose with the largest was aconitic acid. The contents of 57 species decreased significantly, such as conduritol β-expoxide, zymosterol, palatinitol, quinic acid, and isohexoic acid, with the least was ketohexose. Overall, this study highlighted the significant influence of biochar in declining disease by regulating soil microbial community, physical and chemical properties, and secondary metabolites in the bayberry rhizosphere, which provided a novel strategy for managing bayberry decline disease.